Empowering older adults at Sekolah Lansia Purbaya through community-based exercise and audio-visual health education for hypertension management - Rosiana Eva Rayanti; Sri Suwartiningsih; Istananda Tirtaning Nugraheni; Gracia Permatasari; Natalia Esti Kristanti; Aura Syafaroh; Marsela Riska Raswandaru; Maria (PERDIKAN (Journal of Community Engagement), 2026)
Early detection and disease prevention are part of the health activities conducted at Sekolah Lansia Purbaya in Salatiga City, Central Java. A health survey on May 20, 2025, revealed that of 29 older women, most participants had hypertension (89.66%). In addition, 65.52% had a body mass index outside the normal range and 58.62% had abdominal obesity. These conditions showing the need of a community service program focusing on blood pressure management. This activity aimed to improve older adults’ understanding of hypertension through audiovisual education and exercise. A service-learning approach was used for 33 participants from Purbaya Senior Citizens’ School in Karangalit, Salatiga City. The activity included health needs assessment, program preparation, implementation, reflection, and evaluation. Participants received health examinations, take part in the Ngadi Salira hypertension exercise, watched the Healthy Heart and Controlled Blood Pressure (SEHATI) educational video, and had a group discussion. Health examinations in July 2025 showed that 60.61% of participants had stage 1 hypertension and 60.61% had abdominal obesity, while most had normal blood glucose, uric acid, and cholesterol levels. After the service-learning, all the participants reported enjoying the exercise session. During the discussion, many expressed interest in continuing the exercise at home and applying the information provided in the educational video. The Ngadi Salira exercise and SEHATI audiovisual serve as educational tools for managing high blood pressure at the Sekolah Lansia Purbaya.